Lighting up the past. The use of light at Skálholt - Atli Rúnarsson 1989- (2017)
The manipulation of light had a profound way on how people perceived their environment. With the introduction of electricity lighting is taken for granted, but it has not always been like this. Walking into a room that had several glass windows would have been quite impressive in 18th century Iceland, being only accustomed to the basic screen windows which barely omitted light through them. A massive amount of material data was unearthed during the excavations at Skálholt from 2002-2007. This included over 9100 fragments of glass, both window and vessel, and multiple lighting equipment. The aim of this thesis is to explore how light was distributed between rooms in the core settlement at Skálholt during the 18th century and whether the distribution had any relation to the function of the room or if any social factors influenced which rooms had the best lighting. This thesis is based on archaeological finds from the excavation at Skálholt as well as contemporary documentary sources. Along with the analysis some of the prevailing theories concerning the everyday use of light and the social importance of atmosphere will be considered and applied to the research.